Khazanah Leksikon Ke-Pena-An dalam Bahasa Dawan Malaka - Emeliana Tai (BLAZE : Jurnal Bahasa dan Sastra dalam Pendidikan Linguistik dan Pengembangan, 2024)
Indonesia is a country that is nicknamed as an archipelagic country which is rich in identity in the form of various cultures, ethnicities, and traditions. Each region has its own characteristics that can be seen in its cultural system, as well as the Dawan Language Speech Guyub raises two problem formulations related to ecolinguistics, namely the grammatical categories of lexicons of subject in Dawan language, the dimensions of the social praxis function of the Ke -an in Dawan Malaka language. Purpose To analyze the grammatical categories of lexicons of pen in Dawan Malaka language. Analyzing the dimensions of the function of the social praxis lexicon Ke-pen-an in Dawan Malaka language. The theory used is ecolinguistic theory and semantic theory. Qualitative research is used in this research. Data collection was carried out by observation, interview and recording methods. Methods and techniques for analyzing data in this study using qualitative data analysis methods, namely making field notes, collecting, sorting, classifying and then categorizing them into three categories, namely noun categories, verb categories and subjective categories. As well as associated with the dimensions of the social praxis function based on the theory used. Study the results of data analysis using deductive and inductive techniques. The results of the research show that the Khazana lexicon of pens in the Dawan Malaka language. There are 50 lexicons for noun categories, 22 lexicons for verb categories, and 50 lexicon for adjective categories. The 8 (eight) biotic categories of the lexicon are baaf, tauf, nook, sufu, botof, rikuf, poat, pen fua. While the other lexicons from the noun verb category come from the abiotic environment. Relating to the social practical lexicon of pens in the form of Dawan's proverbs. There are 18 personals.